Characterization of Buffalo Dairy Production Systems in Egypt Using Cluster Analysis Procedure (Journal of Buffalo Science, 2019)
The study objective was to characterize and classify buffalo dairy production systems in Egypt. Ten governorates having high buffalo population density were selected as the study area. The data were collected from 1811 dairy buffalo farms using survey. Buffalo holders were face to face interviewed by constructed questionnaire. The survey was applied in two years (2010 and 2011). Two-Step Cluster procedure (CA) was used and analysis was repeated several times until the cluster quality came good (average silhouette ≥0.5). The algorithm selected the number of clusters, after calculating the Akaike’s information criterion (AIC). Statistics of CA showed that the numbers of farm in each cluster were 43 (2.4%) in cluster1 (CL1), 1364 (75.3%) in cluster2 (CL2) and 404 (22.3%) in cluster3 (CL3). CL1 farms had a good availability of facilities. The management practices were the higher in comparison with the farms in the other clusters. Management and feeding systems practices in CL1 ranged from medium to high. CL2 was the largest, with 1364 farms located in all the ten governorates. The availability of facilities and equipment were low or lacking. The management practices were the lowest in comparison with farms in other clusters. CL3 facilities availability were low to medium. The management practices were medium when compared with the farms in the other clusters. The results of the current study demonstrate the existence of a large variability among buffalo dairy production systems in Egypt. These systems variability should be taken into consideration for sustainable system development.